2017
DOI: 10.1136/thoraxjnl-2017-210030
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for endogenous mitochondrial formylated peptide-driven formyl peptide receptor 1 signalling in acute respiratory distress syndrome

Abstract: BackgroundAcute respiratory distress syndrome (ARDS) is an often fatal neutrophil-dominant lung disease. Although influenced by multiple proinflammatory mediators, identification of suitable therapeutic candidates remains elusive. We aimed to delineate the presence of mitochondrial formylated peptides in ARDS and characterise the functional importance of formyl peptide receptor 1 (FPR1) signalling in sterile lung inflammation.MethodsMitochondrial formylated peptides were identified in bronchoalveolar lavage fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 38 publications
(39 reference statements)
2
69
0
Order By: Relevance
“…Our data demonstrating that these host-derived formylated MCTs are highly potent in activating neutrophils support the notion that, when released from disintegrating mitochondria, these molecules may play important roles in the inflammatory response resulting from tissue injury (21,23,24). Indeed, elevated levels of mitochondrialderived formyl peptides have been detected in bronchoalveolar lavage fluid and serum in patients with acute respiratory distress syndrome (54). Activation of circulating neutrophils by mitochondrialderived formyl peptides during cell damage has also been described in trauma patients and has been the suggested cause of systemic inflammatory response syndrome with sepsis-like clinical manifestations (25).…”
Section: Discussionsupporting
confidence: 83%
“…Our data demonstrating that these host-derived formylated MCTs are highly potent in activating neutrophils support the notion that, when released from disintegrating mitochondria, these molecules may play important roles in the inflammatory response resulting from tissue injury (21,23,24). Indeed, elevated levels of mitochondrialderived formyl peptides have been detected in bronchoalveolar lavage fluid and serum in patients with acute respiratory distress syndrome (54). Activation of circulating neutrophils by mitochondrialderived formyl peptides during cell damage has also been described in trauma patients and has been the suggested cause of systemic inflammatory response syndrome with sepsis-like clinical manifestations (25).…”
Section: Discussionsupporting
confidence: 83%
“…Recently, FPR1 was shown to promote pulmonary injury in a mouse model of acute respiratory distress syndrome, 23 Figure 5D). Altogether, these data show that FPR1 expression on graft-infiltrating cells is sufficient to promote graft tissue damage.…”
Section: Fpr1 Promotes Lung Transplant-mediated Ischemia-reperfusiomentioning
confidence: 95%
“…Recently, FPR1 was shown to promote pulmonary injury in a mouse model of acute respiratory distress syndrome, 23 but whether it promotes inflammatory responses to lung transplants remains to be determined. Accordingly, we assessed lung graft injury in mouse recipients treated with cyclosporine H (Cy-H), an FPR1 inhibitor.…”
Section: Fpr1 Promotes Lung Transplant-mediated Ischemia-reperfusiomentioning
confidence: 99%
“…FPRs constitute a small group of 7-transmembrane domain, G-protein-coupled receptors that are expressed not only on neutrophils, monocytes and dendritic cells but also on hepatocytes, endothelial cells and cells of the nervous system (He and Ye, 2017). Indeed, a recent study has suggested a pathogenic role of mitochondrial NFPs in human disease (Dorward et al, 2017). In this study, mitochondrial NFPs appear to be increased in the intra-alveolar space of lungs and circulation of patient with acute respiratory destress syndrome (ARDS) and mitochondrial NFPs-driven formyl peptide receptor 1 signaling seems to mediate an important role in the pathogenesis of sterile lung inflammation (Dorward et al, 2017).…”
Section: Inflammation and Mitochondriamentioning
confidence: 99%
“…Indeed, a recent study has suggested a pathogenic role of mitochondrial NFPs in human disease (Dorward et al, 2017). In this study, mitochondrial NFPs appear to be increased in the intra-alveolar space of lungs and circulation of patient with acute respiratory destress syndrome (ARDS) and mitochondrial NFPs-driven formyl peptide receptor 1 signaling seems to mediate an important role in the pathogenesis of sterile lung inflammation (Dorward et al, 2017). …”
Section: Inflammation and Mitochondriamentioning
confidence: 99%